Foreign ownership, efficiency and solvency: analysis of takaful firms in the GCC region - Adewale, Abideen Adeyemi; Hamid, Zarinah; Asafa, Dauda Adeyinka (ISTAC, 2015)
The financial sector regulatory reforms undertaken by the respective governments of the GCC countries in recent years have liberalized their financial policies and encouraged the influx of foreign-owned firms participating in the Takaful market. This development among others has created a competitive environment for continuous growth and impressive performance of the sector. This paper attempts to examine the efficiency of foreign-owned, vis-à-vis, the domestic owned, Takaful firms while taking into consideration the financial soundness of each Takaful firm. Mathematical programming non-parametric data envelopment analysis (DEA) with range adjustment measures (RAM) are utilized for analyzing 80 selected Takaful firms operating in the region for a 4-year period (2009-2012). Subsequent investigation is conducted using non-parametric statistical measure (Mann Whitney U rank statistics) and latent growth curve modeling to determine the statistically significant differences between the two. Result shows difference in efficiency between the foreign owned and domestically owned Takaful firms in years 2010 and 2012 for the models that include and exclude solvency ratio respectively. The result is actually consistent with the proposition of the global advantage hypothesis which also clearly demonstrates that solvency ratio has moderating influence on the efficiency differences.